2020
DOI: 10.1111/jan.14565
|View full text |Cite
|
Sign up to set email alerts
|

Peripheral intravenous catheter non‐infectious complications in adults: A systematic review and meta‐analysis

Abstract: Aims The aim of this systematic review and meta‐analysis was to summarize and quantify peripheral intravenous catheter‐related complications. Design This systematic review is reported by means of the Cochrane process for randomized controlled trials and the Meta‐analysis of Observation Studies in Epidemiology for cohort studies. Data sources The Cochrane Central Register of Controlled Trials, PubMed, CINAHL and EMBASE databases, clinical trial registries such as ClinicalTrials.gov and the reference list of inc… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

4
67
0
2

Year Published

2021
2021
2024
2024

Publication Types

Select...
8
1

Relationship

2
7

Authors

Journals

citations
Cited by 103 publications
(102 citation statements)
references
References 143 publications
(121 reference statements)
4
67
0
2
Order By: Relevance
“…In this study, during phase one, a high complication rate (26%) was identified mainly due to infiltration and phlebitis, which are the two most reported complications internationally [52]. This finding is lower than most studies conducted in Portugal, with complications rates varying between 50% and 62.1% [33,34,39,53], although none of the studies was conducted in an oncology setting.…”
Section: Discussionmentioning
confidence: 57%
“…In this study, during phase one, a high complication rate (26%) was identified mainly due to infiltration and phlebitis, which are the two most reported complications internationally [52]. This finding is lower than most studies conducted in Portugal, with complications rates varying between 50% and 62.1% [33,34,39,53], although none of the studies was conducted in an oncology setting.…”
Section: Discussionmentioning
confidence: 57%
“…PIVC failure is a frequent complication of PIVC use, with ~40 -70% of these catheters removed prematurely due to mechanical and chemical complications (i.e. phlebitis, dislodgement, occlusion, infiltration) or infection before the completion of scheduled intravenous therapy [3][4][5] .…”
Section: Introductionmentioning
confidence: 99%
“…Currently, short peripheral venous catheters (PVCs) are commonly used for intravenous infusion in hospitals, with a utilization rate as high as 70%. 1 However, for such an important device PVCs remain highly susceptible to complications resulting in catheter failure, which has been reported in individual studies to be as high as 69%, but worldwide literature has never been systematically synthesized which may lead to an underappreciation of these rates. 2 Phlebitis has the highest incidence, accounting for 24% of all complications, 1 and the physical and chemical properties of the drugs being used is one of the main risk factors for phlebitis.…”
Section: Introductionmentioning
confidence: 99%
“…1 However, for such an important device PVCs remain highly susceptible to complications resulting in catheter failure, which has been reported in individual studies to be as high as 69%, but worldwide literature has never been systematically synthesized which may lead to an underappreciation of these rates. 2 Phlebitis has the highest incidence, accounting for 24% of all complications, 1 and the physical and chemical properties of the drugs being used is one of the main risk factors for phlebitis. Yanhong Wang studied the limit time of chemical phlebitis caused by strong acid drug amiodarone.…”
Section: Introductionmentioning
confidence: 99%